Streambank Erosion Mapping on the Nottoway River Using GPS-based Above-water Video - Emine Fidan (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
This project concerns the development of streambank erosion maps on military installations utilizing GPS-based above-water video mapping and image georeferencing techniques. The river mapped was the Nottoway River at the Fort Pickett military installation on October 10-11, 2015. Kayak-mounted above-water cameras were utilized to capture georeferenced images of streambank erosion. These GIS-based erosion classifications were utilized to develop erosion maps for determining streambank erosion conditions along the river. Areas of high erosion were identified as about two percent of the river (2167 ft. of streambank length). These maps allow for the opportunity to revisit the sites to determine changes in streambank erosion due to human impacts. Three sites (encompassing 1118 ft. of streambank) were determined to be areas of high erosion, for future river rehabilitation.
Keywords: GIS; erosion assessment; streambank erosion; sediment pollution; river stability